Albul de plumb – sinteză și caracterizare - Măruțoiu, Constantin; Nemeș, Olivia-Florena (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
Lead white is a salt, containing carbonate and hydroxide ions. Lead white is found as a mineral in nature and is known as cerrusite. The pigment has been used in art since ancient times, gaining great popularity in classical European oil painting, being removed (or rarely used) in modern times due to its toxicity, degradation due to chemical instability under certain conditions and the emergence of modern synthetic pigments. cheap and with good properties. In this paper we present the synthesis of the pigment in the laboratory for study and use in restoration works where it is desired to preserve the original appearance and authenticity of the work of art by using the appropriate materials. The synthesized pigment was applied on different substrates and was analyzed by FTIR reflectance spectroscopy (using a Bruker Alpha II device with a specialized front unit for paintings) and X-ray fluorescence analysis (using a Bruker S1 TITAN series spectrometer). The obtained spectra were analyzed to identify the specific bands described in the literature. Pigment degradation was studied by reaction with hydrogen sulfide and an example of degradation of a historical material from the team’s investigative experience was presented.